What is the Truck Factor of popular GitHub applications? A first assessment - Avelino,Guilherme; Valente,Marco Tulio; Hora,Andre (PeerJ PrePrints, 2015)
The Truck Factor designates the minimal number of developers that have to be hit by a truck (or quit) before a project is incapacitated. It can be seen as a measurement of the concentration of information in individual team members. We calculate the Truck Factor for 133 popular GitHub applications, in six languages. To infer the authors of a file we use the Degree-of-Authorship (DOA) metric, which is computed using version history data, and to estimate the Truck Factor, we use a greedy heuristic. Results show that most systems have a small truck factor (46% have Truck Factor=1 and 28% have Truck Factor=2).
Keywords: Truck Factor; Code Authorship; GitHub; Open source software; Agile Programming